Board Certification Characteristics of Practicing Neuroradiologists - Rosenkrantz, A.B. (AJNR Am J Neuroradiol, 2019)
BACKGROUND AND PURPOSE: Insight into the status of neuroradiology subspecialty certification across the United States could help to understand neuroradiologists' perceived value of subspecialty certification as well as guide efforts to optimize pathways for broader voluntary certification participation. Our aim was to assess board certification characteristics of practicing US neuroradiologists. MATERIALS AND METHODS: The American Board of Radiology public search engine was used to link Medicare-participating radiologists with American Board of Radiology diplomates. Among linked diplomates, 4670 neuroradiologists were identified on the basis of 3 criteria: current or prior neuroradiology subspecialty certification or currently >50% clinical work effort in neuroradiology based on work relative value unit–weighted national Medicare claims (“majority-practice neuroradiologists”). Subspecialty certification status was studied in each group, using Centers for Medicare & Medicaid Services data to identify additional physician characteristics. RESULTS: Of 3769 included radiologists ever subspecialty certified, 84.1% are currently subspecialty certified. Of 1777/3769 radiologists ever subspecialty-certified and with lifetime primary certificates (ie, nonmandated Maintenance of Certification), only 66.6% are currently subspecialty certified. Of 3341 included majority-practice neuroradiologists, 73.0% were ever subspecialty certified; of these, 89.1% are currently subspecialty certified. Of 3341 majority-practice neuroradiologists, the fraction currently subspecialty certified was higher for those in academic (81.3%) versus nonacademic (58.2%) practices, larger versus smaller practices (72.1% for those in ≥100 versus 36.1% for <10-member practices), US regions other than the West (64.1%–70.6% versus 56.5%), fewer years in practice (77.5% for 11–20 years versus 31.3% for >50 years), and time-limited (73.5%) versus lifetime (54.9%) primary certificates. CONCLUSIONS: More than one-quarter of majority-practice neuroradiologists never obtained neuroradiology subspecialty certification. Even when initially obtained, that certification is commonly not maintained, particularly by lifetime primary certificate diplomates and those in nonacademic and smaller practices. Further investigation is warranted to better understand neuroradiologists' decisions regarding attaining and maintaining subspecialty certification.